Antistatic and corrosion-resistant nitrile gloves and preparation method thereof

By using modified epoxy resin, carboxy-based nitrile latex and reinforcement additives, anti-static and corrosion-resistant nitrile gloves are prepared, which solves the problem of degradation of glove performance in the prior art and achieves higher anti-static, corrosion-resistant and tensile properties.

CN118580589BActive Publication Date: 2025-04-29GAOZHOU YONGLI LABOR PROTECTION PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410782579.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-04-29
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

Existing nitrile gloves cause increased hardness, reduced flexibility and tensile properties of gloves after adding conductive materials, while insufficient anti-static and corrosion resistance.

Method used

Modified epoxy resin and carboxy-based nitrile latex are used as the main raw materials, combined with enhancement additives and modified nanoparticles, and the anti-static, corrosion-resistant and tensile properties of the gloves are improved by preparing the immersion latex and optimizing the preparation method.

Benefits of technology

It effectively improves the anti-static, tensile, corrosion and wear resistance of nitrile gloves, and solves the problems of increased hardness and reduced performance of gloves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004897598100000021
    Figure BDA0004897598100000021
  • Figure BDA0004897598100000031
    Figure BDA0004897598100000031
  • Figure BDA0004897598100000041
    Figure BDA0004897598100000041
Patent Text Reader

Abstract

The invention discloses an antistatic and corrosion-resistant nitrile glove and a preparation method thereof, belongs to the technical field of nitrile glove processing, and is used to solve the problem that the tensile performance of the nitrile glove decreases due to the addition of conductive materials to the nitrile glove in the prior art, and the antistatic performance and corrosion resistance of the nitrile glove need to be further improved; the invention comprises the following components in parts by weight: 30-40 parts of modified epoxy resin, 70-80 parts of carboxyl nitrile latex, 20-30 parts of reinforcing aid, 130-150 parts of tetrahydrofuran and 2-3 parts of additive; the invention strengthens the carboxyl nitrile latex by preparing polymethacrylic glycidyl ester modified with fluorine-containing chain segments and the reinforcing aid, optimizes the preparation method of the nitrile glove, effectively improves the antistatic performance of the nitrile glove, and also improves the tensile performance, corrosion resistance and wear resistance of the nitrile glove.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nitrile glove processing, and in particular to an antistatic and corrosion-resistant nitrile glove and a preparation method thereof. Background Art

[0002] Nitrile gloves are made of nitrile rubber as the main raw material. They have excellent oil resistance, chemical corrosion resistance and good physical properties. In modern industrial production, medical and health care, scientific research experiments and other fields, gloves are an important protective product with increasingly higher performance requirements, especially for those who need to work in special environments, such as the chemical industry, electronics industry, medical surgery, etc. The gloves not only need to have good protective properties, such as corrosion resistance, anti-static, etc., but also need to be comfortable and durable.

[0003] Traditional nitrile gloves have high surface resistance and are prone to accumulate static charges, which can easily cause electrostatic discharge. In some static-sensitive environments, ordinary nitrile gloves are prone to generate static electricity, which may not only interfere with the normal operation of precision instruments, but may even cause electrostatic discharge, leading to dangerous accidents and causing damage to sensitive electronic components or flammable and explosive substances.

[0004] However, some antistatic or corrosion-resistant nitrile glove products in the prior art, during the production process, usually during the preparation process of nitrile gloves, conductive materials are added or antistatic coatings are applied to the outside of the gloves. Conductive materials usually have a higher hardness. When they are mixed with soft nitrile latex, the hardness of the entire material increases, which can easily cause the softness, comfort and tensile properties of the gloves to decrease. The antistatic properties of the antistatic coating applied to the outside of nitrile gloves gradually weaken with time and increasing frequency of use, and cannot maintain a stable antistatic effect for a long time. In addition, traditional nitrile gloves are easily damaged when encountering corrosive media such as strong acids and alkalis, which reduces the service life and protective effect. The corrosion resistance of nitrile gloves needs to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide an antistatic and corrosion-resistant nitrile glove and a preparation method thereof, so as to solve the technical problem that the addition of conductive materials to nitrile gloves in the prior art leads to a decrease in the tensile properties of the nitrile gloves, and the antistatic and corrosion resistance of the nitrile gloves need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: an antistatic and corrosion-resistant nitrile glove, comprising the following components in parts by weight: 30-40 parts of modified epoxy resin, 70-80 parts of carboxyl nitrile latex, 20-30 parts of reinforcing additive, 130-150 parts of tetrahydrofuran and 2-3 parts of additive;

[0008] The solid content of the carboxyl nitrile latex is 50-55%;

[0009] The processing method of the modified epoxy resin is as follows: glycidyl methacrylate, perfluorododecylethylene and toluene are added into a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 75-85° C., an initiator is added into the reactor, the reaction is carried out by heat preservation for 6-8 hours, and the modified epoxy resin is obtained by post-processing.

[0010] The synthetic reaction formula of modified epoxy resin is:

[0011]

[0012] The synthetic reaction principle of modified epoxy resin is:

[0013] Under the action of a free radical initiator, free radical polymerization reaction occurs on the olefin double bonds of glycidyl methacrylate and perfluorododecylethylene to generate a modified epoxy resin having a perfluorinated chain segment modified polyglycidyl methacrylate.

[0014] Furthermore, the usage ratio of the initiator of glycidyl methacrylate, perfluorododecylethylene and toluene is 3g:1-2g:15mL:0.02g, the initiator is dibenzoyl peroxide, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is kept at 75-85°C, and the solvent is evaporated under reduced pressure to obtain a modified epoxy resin.

[0015] Furthermore, the preparation method of the reinforcing agent is: adding modified polysiloxane, modified nanoparticles and methanol into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to reflux the system, heat preservation for 2-3 hours, and post-processing to obtain the reinforcing agent.

[0016] The synthetic reaction principle of the reinforcing agent is:

[0017] The modified nanoparticles contain anhydride, which has two carboxylic acid groups, and can undergo ring opening and condensation reaction with active groups such as amino groups and hydroxyl groups on the modified polysiloxane, thereby promoting the combination of the modified polysiloxane and the modified nanoparticles to prepare a reinforcing agent.

[0018] Furthermore, the usage ratio of the modified polysiloxane, the modified nanoparticles and methanol is 3g:2g:30mL, and the post-treatment includes: after the reaction is completed, the reactor is kept warm and refluxed, and the solvent is evaporated under reduced pressure to obtain a reinforcing agent.

[0019] Further, the modified polysiloxane is obtained by processing the following steps:

[0020] A1. Add isocyanatepropyltriethoxysilane, dopamine hydrochloride and tetrahydrofuran solution into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to reflux the system, keep the temperature for 4-6 hours, and perform post-treatment to obtain modified siloxane.

[0021] The synthetic reaction formula of modified siloxane is:

[0022]

[0023]

[0024] The synthetic reaction principle of modified siloxane is:

[0025] The isocyanate group on isocyanatepropyl triethoxysilane and the amino group on dopamine hydrochloride are active groups, and a condensation reaction occurs in a tetrahydrofuran solution. By adding sodium hydroxide to the tetrahydrofuran solution, the hydrochloric acid in the dopamine hydrochloride can be reacted to generate sodium chloride, thereby promoting the solubility of dopamine hydrochloride in tetrahydrofuran, making the synthesis reaction of the modified siloxane easier to proceed, and preparing triethoxysilane modified with dopamine.

[0026] A2. Add aminopropylmethyldiethoxysilane, octamethylsilicone oil, modified siloxane and tetrahydrofuran into a reaction kettle and stir. Increase the temperature of the reaction kettle to reflux the system. Add potassium hydroxide solution into the reaction kettle and keep the temperature to react for 10-12 hours. Post-treat to obtain modified polysiloxane.

[0027] The synthetic reaction formula of modified polysiloxane is:

[0028]

[0029] In the formula

[0030] The synthetic reaction principle of modified polysiloxane is:

[0031] Under high temperature environment, potassium hydroxide is used as a catalyst to catalyze the disconnection of the siloxane bonds on aminopropylmethyldiethoxysilane and modified siloxane, and initiate the anionic ring opening of octamethyl silicone oil, resulting in a condensation reaction to form a modified polysiloxane with aminopropylmethyldiethoxysilane and modified siloxane blocks.

[0032] Further, in step A1, the tetrahydrofuran solution is composed of sodium hydroxide and tetrahydrofuran in a ratio of 1g:10mL, the isocyanatepropyl triethoxysilane and dopamine hydrochloride in a ratio of 1mol:1mol, and the hydrochloric acid dopamine and tetrahydrofuran solution in a ratio of 1g:10mL, and the post-treatment operation includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filtrate is transferred to a rotary evaporator with a water bath temperature of 45-50°C, and the solvent is evaporated under reduced pressure to obtain a modified siloxane; in step A2, the aminopropyl methyl diethoxysilane The amount ratio of alkane, octamethyl silicone oil, modified siloxane, tetrahydrofuran and potassium hydroxide solution is 1g:3g:1g:20mL:7mL, the mass concentration of the potassium hydroxide solution is 10-15%, and the post-treatment comprises: after the reaction is completed, the reactor is kept warm and refluxed, the solvent is evaporated, the temperature of the reactor is lowered to room temperature, purified water and chloroform are added to the reactor, stirred at room temperature for 10-15min, allowed to stand for separation, the organic phase is washed 3 times with purified water and then transferred to a rotary evaporator with a water bath temperature of 40-50°C, and the solvent is evaporated under reduced pressure to obtain modified polysiloxane.

[0033] Furthermore, the modified nanoparticles are obtained by processing the following steps:

[0034] B1. Add nano zinc oxide, 5-hexenyltrimethoxysilane and anhydrous ethanol into a reactor, disperse by ultrasonic for 30-50 minutes and then stir, add sodium hydroxide solution into the reactor, increase the temperature of the reactor to 50-60°C, keep the temperature for 5-7 hours, and perform post-treatment to obtain activated nanoparticles;

[0035] The synthetic reaction formula of activated nanoparticles is:

[0036]

[0037] Wherein, · is nano zinc oxide.

[0038] The synthetic reaction principle of activated nanoparticles is:

[0039] Sodium hydroxide is used as a catalyst to promote the opening of the siloxane bond on 5-hexenyltrimethoxysilane, forming silanol groups and undergoing condensation reactions with active oxygen-containing functional groups on the surface of nano-silicon dioxide to form chemical bonds, thereby connecting the organic groups to the surface of nano-zinc oxide to obtain activated nanoparticles.

[0040] B2. Add activated nanoparticles, 1-allyl-3-methylimidazolium chloride, maleic anhydride, N,N-dimethylformamide and initiator into a reactor and stir. Raise the temperature of the reactor to 55-65°C and keep the reaction temperature for 6-8 hours. Post-treat to obtain modified nanoparticles.

[0041] The synthetic reaction formula of modified nanoparticles is:

[0042]

[0043] The synthetic reaction principle of modified nanoparticles is:

[0044] After activated nanoparticles, 1-allyl-3-methylimidazolium chloride and maleic anhydride are uniformly mixed in N,N-dimethylformamide, under the action of an initiator, the olefin double bond is disconnected and a free radical polymerization reaction occurs, and a coating layer of polyolefin modified with anhydride and methylimidazolium chloride is formed on the outside of the nanoparticles to prepare modified nanoparticles.

[0045] Furthermore, in step B1, the dosage ratio of the nano zinc oxide, 5-hexenyltrimethoxysilane, anhydrous ethanol and sodium hydroxide solution is 3g:1g:15mL:5mL, the concentration of the sodium hydroxide solution is 0.1-0.2mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C and dried to constant weight to obtain activated nanoparticles; In step B2, the amount ratio of the activated nanoparticles, 1-allyl-3-methylimidazolium chloride, maleic anhydride, N,N-dimethylformamide and initiator is 3g:2g:1g:20mL:0.05g, the initiator is azobisisobutyronitrile, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with anhydrous ethanol for 3 times and then dried, and the filter cake is transferred to a drying oven at a temperature of 50-60°C and dried to constant weight to obtain modified nanoparticles.

[0046] A method for preparing antistatic and corrosion-resistant nitrile gloves comprises the following steps:

[0047] S1, adding modified epoxy resin, carboxyl nitrile latex, reinforcing agent, tetrahydrofuran and additives into a reactor and stirring, raising the temperature of the reactor to 50-55° C., keeping warm and stirring for 20-30 minutes, passing through an 80-mesh sieve to obtain a dipped latex;

[0048] S2, cleaning and drying the hand mold, immersing the hand mold in a demoulding liquid to form a film layer on the outside of the hand mold to obtain a pretreated hand mold;

[0049] S3, immersing the pretreated hand mold in a dipping latex, and after the dipping latex is leached out, immersing it in a coagulation bath to form a uniform film on the outside of the hand mold, and post-treating to obtain a nitrile film;

[0050] S4, curling the nitrile film to form an elastic rubber ring at the wrist of the glove, closing the mold, and heat-setting to obtain a crude nitrile glove;

[0051] S5, washing the crude nitrile gloves with chlorine, drying them, and then demoulding them to obtain nitrile gloves.

[0052] Furthermore, in step S1, the additives are composed of an antioxidant, a dispersant and a plasticizer in a weight ratio of 1:1:3, the antioxidant is one or more combinations of antioxidant RD, antioxidant BLE and antioxidant D, the dispersant is one or more combinations of zinc stearate, sodium stearate, calcium stearate and magnesium stearate, and the plasticizer is a phthalate; in step S2, the demoulding liquid is an 8-10wt% calcium chloride solution, and the temperature of the demoulding liquid is 55-65°C; in step S3, the coagulation bath is composed of calcium nitrate, starch, gum arabic, phenol and soft water in a weight ratio of 40:1.5:1:0 .5:150, the post-treatment includes: washing the film twice with soft water, and after each washing, using compressed air purified by a 3M filter to blow dry the water stains on the surface of the film to obtain a nitrile film; in step S4, the heat setting temperature is 115-125°C; in step S5, the chlorine washing and drying operations are: completely immersing the hand mold with the crude nitrile gloves on the outside in a chlorine solution with an active chlorine content of 500-1000 mg / L, ultrasonically treating for 15-25s, washing twice with soft water, and after each washing, using compressed air purified by a 3M filter to blow dry its surface.

[0053] The present invention has the following beneficial effects:

[0054] 1. The antistatic and corrosion-resistant nitrile gloves of the present invention are prepared by mixing carboxyl nitrile latex as a raw material with a modified epoxy resin having a perfluorinated segment-modified polymethacrylic glycidyl ester, and then using a reinforcing agent as a reinforcing agent to perform reinforcing modification to prepare a dipping latex. By optimizing the preparation method of the nitrile gloves, not only the antistatic properties of the nitrile gloves are effectively improved, but also the tensile properties, corrosion resistance and wear resistance of the nitrile gloves are improved.

[0055] 2. The antistatic and corrosion-resistant nitrile gloves of the present invention are prepared by preparing modified zinc oxide nanoparticles coated with polyolefin modified with acid anhydride and methylimidazole chloride, and then reacting the modified zinc oxide nanoparticles with modified polysiloxane segments modified with dopamine and amino groups under a high temperature environment to promote the combination of the modified polysiloxane and the modified nanoparticles to prepare a reinforcing agent; zinc oxide itself has good antibacterial, conductive and chemical resistance properties, and the dispersibility of zinc oxide in the latex is improved by coating and modifying the outside of the zinc oxide, thereby improving the antistatic performance of the nitrile gloves, and dopamine molecules are grafted on the polysiloxane segments. , which can enhance its compatibility and interaction with modified nanoparticles and carboxyl nitrile latex matrix, help nano zinc oxide particles to be more evenly dispersed in the matrix, form a more stable conductive network, improve the cross-linking degree of nitrile gloves, and thus improve the tensile properties of the material. Nano zinc oxide is added to nitrile latex materials as inorganic particles to improve the wear resistance of the material; 1-allyl-3-methylimidazolium chloride, as an ionic salt, has strong electrophilicity and nucleophilicity, which enables it to cooperate with nanoparticles, promote the dispersion and conduction of charges in the glove material, and further improve the antistatic properties of nitrile gloves.

[0056] 3. The antistatic and corrosion-resistant nitrile gloves of the present invention are prepared by preparing a modified epoxy resin having a perfluorinated segment-modified polymethacrylic glycidyl ester. The epoxy groups on the modified epoxy resin can react with the active groups in the dipping latex to form a new cross-linked structure, thereby improving the tensile properties and wear resistance of the nitrile gloves. The zinc oxide itself has excellent corrosion resistance. After a layer of polyolefin is coated on the outside, a polysiloxane having good softness, lubricity and chemical stability is coated on the outside, and then the modified epoxy resin and the carboxyl nitrile latex are coordinated with each other, which is helpful to further improve the corrosion resistance of the nitrile gloves. The tensile properties and corrosion resistance of the base latex are improved, and perfluorinated segments are introduced into the modified epoxy resin. The perfluorinated segments have high chemical stability and can resist corrosion from a variety of chemical substances. During the preparation and curing process of the nitrile composite latex, surface migration occurs due to the difference in intermolecular force and surface tension between the perfluorinated segments and the latex, so as to reduce the surface energy of the overall system. When preparing nitrile gloves, by controlling the temperature of the dipping latex and the heat setting temperature, the fluorinated segments are promoted to aggregate to the outside of the gloves to form a fluorine-modified layer, thereby further improving the corrosion resistance and wear resistance of the material. DETAILED DESCRIPTION

[0057] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Example 1

[0059] This embodiment provides a method for preparing an antistatic and corrosion-resistant dipping latex for processing nitrile gloves, comprising the following steps:

[0060] S1. Preparation of modified polysiloxane

[0061] Mix sodium hydroxide and tetrahydrofuran in a ratio of 1 g:10 mL to obtain a tetrahydrofuran solution for later use;

[0062] Weigh: 247.4 g of isocyanatepropyltriethoxysilane, 189.6 g of dopamine hydrochloride and 1896 mL of tetrahydrofuran solution, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature to react for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 45°C, and evaporate the solvent under reduced pressure to obtain modified siloxane;

[0063] Weigh: 50 g of aminopropylmethyldiethoxysilane, 150 g of octamethylsilicone oil, 50 g of modified siloxane, and 1000 mL of tetrahydrofuran, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 350 mL of 10 wt % potassium hydroxide solution to the reactor, and keep the reaction for 10 hours. After the reaction is completed, keep the reactor at reflux, evaporate the solvent, lower the temperature of the reactor to room temperature, add 800 mL of purified water and 1000 mL of chloroform to the reactor, stir at room temperature for 10 minutes, stand and separate the liquids, wash the organic phase with purified water three times, transfer it to a rotary evaporator with a water bath temperature of 40°C, and evaporate the solvent under reduced pressure to obtain a modified polysiloxane.

[0064] S2. Preparation of modified nanoparticles

[0065] Weigh: 300g of nano zinc oxide, 100g of 5-hexenyltrimethoxysilane, and 1500mL of anhydrous ethanol, add them into a reactor, stir after ultrasonic dispersion for 30min, add 500mL of 0.1mol / L sodium hydroxide solution into the reactor, raise the temperature of the reactor to 50°C, and keep the reaction for 5h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at 60°C, and dry it to constant weight to obtain activated nanoparticles;

[0066] Weigh: 300 g of activated nanoparticles, 200 g of 1-allyl-3-methylimidazole chloride, 100 g of maleic anhydride, 2000 mL of N,N-dimethylformamide and 5 g of azobisisobutyronitrile, add into a reactor and stir, raise the temperature of the reactor to 55°C, and keep the reaction for 6 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 50°C, and dry it to constant weight to obtain modified nanoparticles.

[0067] S3. Preparation of reinforcing additives

[0068] Weigh: 300 g of modified polysiloxane, 200 g of modified nanoparticles and 3000 mL of methanol, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to reflux the system, and keep it warm for 2 hours. After the reaction is completed, keep the reactor warm and reflux, and evaporate the solvent under reduced pressure to obtain a reinforcing agent.

[0069] S4. Preparation of modified epoxy resin

[0070] Weigh: 300 g of glycidyl methacrylate, 100 g of perfluorododecylethylene and 1500 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 75°C, add 2 g of dibenzoyl peroxide into the reactor, and keep the reaction for 6 hours. After the reaction is completed, keep the reactor temperature at 75°C, and evaporate the solvent under reduced pressure to obtain a modified epoxy resin.

[0071] S5, prepare dipping latex

[0072] The antioxidant RD, zinc stearate and dioctyl phthalate are uniformly mixed in a weight ratio of 1:1:3 to obtain an additive for standby use;

[0073] Weigh by weight: 30 parts of modified epoxy resin, 70 parts of carboxylated nitrile latex, 20 parts of reinforcing agent, 130 parts of tetrahydrofuran and 2 parts of additives, add into the reactor and stir, raise the temperature of the reactor to 50°C, keep warm and stir for 20 minutes, pass through an 80-mesh sieve to obtain a dipping latex.

[0074] Example 2

[0075] This embodiment provides a method for preparing an antistatic and corrosion-resistant dipping latex for processing nitrile gloves, comprising the following steps:

[0076] S1. Preparation of modified polysiloxane

[0077] Mix sodium hydroxide and tetrahydrofuran in a ratio of 1 g:10 mL to obtain a tetrahydrofuran solution for later use;

[0078] Weigh: 247.4 g of isocyanatepropyltriethoxysilane, 189.6 g of dopamine hydrochloride and 1896 mL of tetrahydrofuran solution, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature to react for 5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 47° C., and evaporate the solvent under reduced pressure to obtain modified siloxane;

[0079] Weigh: 50 g of aminopropylmethyldiethoxysilane, 150 g of octamethylsilicone oil, 50 g of modified siloxane, and 1000 mL of tetrahydrofuran, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 350 mL of 13 wt % potassium hydroxide solution to the reactor, and keep the reaction for 11 hours. After the reaction is completed, keep the reactor at reflux, evaporate the solvent, lower the temperature of the reactor to room temperature, add 800 mL of purified water and 1000 mL of chloroform to the reactor, stir at room temperature for 13 minutes, stand and separate the liquids, wash the organic phase with purified water three times, transfer it to a rotary evaporator with a water bath temperature of 45°C, and evaporate the solvent under reduced pressure to obtain a modified polysiloxane.

[0080] S2. Preparation of modified nanoparticles

[0081] Weigh: 300g of nano zinc oxide, 100g of 5-hexenyltrimethoxysilane, and 1500mL of anhydrous ethanol, add them into a reactor, stir after ultrasonic dispersion for 40min, add 500mL of 0.15mol / L sodium hydroxide solution into the reactor, raise the temperature of the reactor to 55°C, and keep the reaction for 6h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, and dry to constant weight to obtain activated nanoparticles;

[0082] Weigh: 300 g of activated nanoparticles, 200 g of 1-allyl-3-methylimidazole chloride, 100 g of maleic anhydride, 2000 mL of N,N-dimethylformamide and 5 g of azobisisobutyronitrile, add into a reactor and stir, raise the temperature of the reactor to 60°C, and keep the reaction for 7 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 55°C, and dry it to constant weight to obtain modified nanoparticles.

[0083] S3. Preparation of reinforcing additives

[0084] Weigh: 300 g of modified polysiloxane, 200 g of modified nanoparticles and 3000 mL of methanol, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to reflux the system, and keep it warm for 2.5 hours. After the reaction is completed, keep the reactor warm and reflux, and evaporate the solvent under reduced pressure to obtain a reinforcing agent.

[0085] S4. Preparation of modified epoxy resin

[0086] Weigh: 300 g of glycidyl methacrylate, 150 g of perfluorododecylethylene and 1500 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 80°C, add 2 g of dibenzoyl peroxide into the reactor, and keep the reaction for 7 hours. After the reaction is completed, keep the reactor temperature at 80°C, and evaporate the solvent under reduced pressure to obtain a modified epoxy resin.

[0087] S5, prepare dipping latex

[0088] The antioxidant BLE, calcium stearate and dibutyl phthalate are uniformly mixed in a weight ratio of 1:1:3 to obtain an additive for standby use;

[0089] Weigh by weight: 35 parts of modified epoxy resin, 75 parts of carboxylated nitrile latex, 25 parts of reinforcing agent, 140 parts of tetrahydrofuran and 2.5 parts of additives, add into the reactor and stir, raise the temperature of the reactor to 53°C, keep warm and stir for 25 minutes, pass through an 80-mesh sieve to obtain a dipping latex.

[0090] Example 3

[0091] This embodiment provides a method for preparing an antistatic and corrosion-resistant dipping latex for processing nitrile gloves, comprising the following steps:

[0092] S1. Preparation of modified polysiloxane

[0093] Mix sodium hydroxide and tetrahydrofuran in a ratio of 1 g:10 mL to obtain a tetrahydrofuran solution for later use;

[0094] Weigh: 247.4 g of isocyanatepropyltriethoxysilane, 189.6 g of dopamine hydrochloride and 1896 mL of tetrahydrofuran solution, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature to react for 6 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, transfer the filtrate to a rotary evaporator with a water bath temperature of 50° C., and evaporate the solvent under reduced pressure to obtain modified siloxane;

[0095] Weigh: 50 g of aminopropylmethyldiethoxysilane, 150 g of octamethylsilicone oil, 50 g of modified siloxane, and 1000 mL of tetrahydrofuran, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 350 mL of 15 wt % potassium hydroxide solution to the reactor, and keep the reaction for 12 hours. After the reaction is completed, keep the reactor at reflux, evaporate the solvent, lower the temperature of the reactor to room temperature, add 800 mL of purified water and 1000 mL of chloroform to the reactor, stir at room temperature for 15 minutes, stand and separate the liquids, wash the organic phase with purified water three times, transfer it to a rotary evaporator with a water bath temperature of 50°C, and evaporate the solvent under reduced pressure to obtain a modified polysiloxane.

[0096] S2. Preparation of modified nanoparticles

[0097] Weigh: 300g of nano zinc oxide, 100g of 5-hexenyltrimethoxysilane, and 1500mL of anhydrous ethanol, add them into a reactor, stir after ultrasonic dispersion for 50min, add 500mL of 0.2mol / L sodium hydroxide solution into the reactor, raise the temperature of the reactor to 60°C, and keep the reaction for 7h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at 70°C, and dry it to constant weight to obtain activated nanoparticles;

[0098] Weigh: 300 g of activated nanoparticles, 200 g of 1-allyl-3-methylimidazole chloride, 100 g of maleic anhydride, 2000 mL of N,N-dimethylformamide and 5 g of azobisisobutyronitrile, add into a reactor and stir, raise the temperature of the reactor to 65°C, and keep the reaction for 8 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 60°C, and dry it to constant weight to obtain modified nanoparticles.

[0099] S3. Preparation of reinforcing additives

[0100] Weigh: 300 g of modified polysiloxane, 200 g of modified nanoparticles and 3000 mL of methanol, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to reflux the system, and keep it warm for 3 hours. After the reaction is completed, keep the reactor warm and reflux, and evaporate the solvent under reduced pressure to obtain a reinforcing agent.

[0101] S4. Preparation of modified epoxy resin

[0102] Weigh: 300 g of glycidyl methacrylate, 200 g of perfluorododecylethylene and 1500 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 85°C, add 2 g of dibenzoyl peroxide into the reactor, and keep the reaction for 8 hours. After the reaction is completed, keep the reactor temperature at 85°C, and evaporate the solvent under reduced pressure to obtain a modified epoxy resin.

[0103] S5, prepare dipping latex

[0104] The antioxidant D, magnesium stearate and diethyl phthalate are uniformly mixed in a weight ratio of 1:1:3 to obtain an additive for later use;

[0105] Weigh by weight: 40 parts of modified epoxy resin, 80 parts of carboxyl nitrile latex, 30 parts of reinforcing agent, 150 parts of tetrahydrofuran and 3 parts of additives, add into the reactor and stir, raise the temperature of the reactor to 55°C, keep warm and stir for 30 minutes, pass through an 80-mesh sieve to obtain a dipping latex.

[0106] Example 4

[0107] This embodiment provides a method for preparing antistatic and corrosion-resistant nitrile gloves, comprising the following steps:

[0108] Step 1: Hand model pretreatment

[0109] The hand mold is cleaned and dried, and then immersed in a demoulding liquid composed of an 8 wt % calcium chloride solution at a temperature of 55° C. to form a film layer on the outside of the hand mold to obtain a pretreated hand mold;

[0110] Step 2: Dipping

[0111] Calcium nitrate, starch, gum arabic, phenol and soft water are mixed uniformly in a weight ratio of 40:1.5:1:0.5:150 to obtain a coagulation bath for later use;

[0112] The pretreated hand mold was immersed in the dipping emulsion with a temperature of 50°C prepared in Example 1. After the dipping emulsion was leached out, it was immersed in a coagulation bath to form a uniform film on the outside of the hand mold. The film was washed twice with soft water, and after each washing, the water stains on the surface of the film were blown dry with compressed air purified by a 3M filter element to obtain a nitrile film.

[0113] Step 3: Preparation of crude nitrile gloves

[0114] The nitrile film is curled to form an elastic rubber ring at the wrist of the glove, and the mold is closed. The mold temperature is increased to 115°C, heat-set for 20 seconds, and cooled to room temperature to obtain a crude nitrile glove.

[0115] Step 4: Prepare nitrile gloves

[0116] The hand mold with the crude nitrile glove on the outside was completely immersed in a chlorine solution with an active chlorine content of 500 mg / L, ultrasonically treated for 15 seconds, washed twice with soft water, and after each washing, the surface was blown dry with compressed air purified by a 3M filter element, and then demolded to obtain the nitrile glove.

[0117] Example 5

[0118] This embodiment provides a method for preparing antistatic and corrosion-resistant nitrile gloves, comprising the following steps:

[0119] Step 1: Hand model pretreatment

[0120] The hand mold is cleaned and dried, and then immersed in a demoulding liquid composed of a 9wt% calcium chloride solution at a temperature of 60°C to form a film layer on the outside of the hand mold to obtain a pretreated hand mold;

[0121] Step 2: Dipping

[0122] Calcium nitrate, starch, gum arabic, phenol and soft water are mixed uniformly in a weight ratio of 40:1.5:1:0.5:150 to obtain a coagulation bath for later use;

[0123] The pretreated hand mold was immersed in the dipping emulsion with a temperature of 53°C prepared in Example 2. After the dipping emulsion was leached out, it was immersed in a coagulation bath to form a uniform film on the outside of the hand mold. The film was washed twice with soft water, and after each washing, the water stains on the surface of the film were blown dry with compressed air purified by a 3M filter element to obtain a nitrile film.

[0124] Step 3: Preparation of crude nitrile gloves

[0125] The nitrile film is curled to form an elastic rubber ring at the wrist of the glove, and the mold is closed. The mold temperature is increased to 120°C, heat-set for 25 seconds, and cooled to room temperature to obtain a crude nitrile glove.

[0126] Step 4: Prepare nitrile gloves

[0127] The hand mold with the crude nitrile glove on the outside was completely immersed in a chlorine solution with an active chlorine content of 750 mg / L, ultrasonically treated for 20 seconds, washed twice with soft water, and after each washing, the surface was blown dry with compressed air purified by a 3M filter element, and then demolded to obtain the nitrile glove.

[0128] Example 6

[0129] This embodiment provides a method for preparing antistatic and corrosion-resistant nitrile gloves, comprising the following steps:

[0130] Step 1: Hand model pretreatment

[0131] The hand mold is cleaned and dried, and then immersed in a demoulding liquid composed of a 10 wt % calcium chloride solution at a temperature of 65° C. to form a film layer on the outside of the hand mold to obtain a pretreated hand mold;

[0132] Step 2: Dipping

[0133] Calcium nitrate, starch, gum arabic, phenol and soft water are mixed uniformly in a weight ratio of 40:1.5:1:0.5:150 to obtain a coagulation bath for later use;

[0134] The pretreated hand mold was immersed in the dipping emulsion with a temperature of 55°C prepared in Example 3. After the dipping emulsion was leached out, it was immersed in a coagulation bath to form a uniform film on the outside of the hand mold. The film was washed twice with soft water, and after each washing, the water stains on the surface of the film were blown dry with compressed air purified by a 3M filter element to obtain a nitrile film.

[0135] Step 3: Preparation of crude nitrile gloves

[0136] The nitrile film is curled to form an elastic rubber ring at the wrist of the glove, and the mold is closed. The mold temperature is increased to 125°C, heat-set for 30 seconds, and cooled to room temperature to obtain a crude nitrile glove.

[0137] Step 4: Prepare nitrile gloves

[0138] The hand mold with the crude nitrile glove on the outside was completely immersed in a chlorine solution with an active chlorine content of 1000 mg / L, ultrasonically treated for 25 seconds, washed twice with soft water, and after each washing, the surface was blown dry with compressed air purified by a 3M filter element, and then demolded to obtain the nitrile glove.

[0139] Comparative Example 1

[0140] The difference between this comparative example and Example 6 is that in Example 3, when preparing the dipping latex, in step S1, during the preparation of the modified polysiloxane, no modified siloxane is added.

[0141] Comparative Example 2

[0142] The difference between this comparative example and Example 6 is that, in Example 3, when preparing the dipping latex, step S2 is omitted, and in step S3, in the process of preparing the reinforcing auxiliary agent, the modified nanoparticles are replaced by nano zinc oxide in step S2.

[0143] Comparative Example 3

[0144] The difference between this comparative example and Example 6 is that, when preparing the dipping latex in Example 3, step S4 is omitted, and in step S5, no modified epoxy resin is added.

[0145] Performance Testing:

[0146] The mechanical properties, antistatic properties, and corrosion resistance of the nitrile gloves prepared in Examples 4-6 and Comparative Examples 1-3 were tested. The antistatic performance was measured according to the standard GB / T 15662-1995 "Test method for volume resistivity of conductive and antistatic plastics" to determine the volume resistivity and surface resistivity of the sample. The mechanical properties were measured according to the standard GB / T 7543-2020 "Disposable sterilized rubber surgical gloves" to determine the minimum tear force, minimum elongation at break, and maximum 300% elongation load of the sample. The corrosion resistance was measured according to the standard HG / T 2584-2010 "Rubber industrial gloves" to determine the penetration resistance of the sample. The specific test results are shown in Table 1:

[0147] Table 1-Performance test data of the sample

[0148]

[0149]

[0150] Data Analysis:

[0151] Comparative analysis of the data in Table 1 shows that the volume resistivity of the nitrile gloves prepared by the present invention reaches 6.1×10 6 Ω·cm, surface resistivity reaches 8.5×10 8 Ω, the minimum breaking force reaches 15.5N, the minimum breaking elongation reaches 855%, the maximum 300% fixed elongation load reaches 3.6N, and it performs excellently in the direction of penetration resistance. All performance test data are better than those of the comparative example, indicating that the present invention is to strengthen the carboxyl nitrile latex by preparing polymethacrylic glycidyl ester modified with fluorine-containing chain segments and reinforcing additives, optimize the preparation method of nitrile gloves, not only effectively improve the antistatic properties of nitrile gloves, but also improve the tensile properties, corrosion resistance and wear resistance of nitrile gloves.

[0152] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0153] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0154] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An antistatic and corrosion-resistant nitrile glove, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of modified epoxy resin, 70-80 parts of carboxylated nitrile latex, 20-30 parts of reinforcing auxiliary agent, 130-150 parts of tetrahydrofuran and 2-3 parts of additives; The solid content of the carboxylated nitrile latex is 50-55%; The processing method of the modified epoxy resin is as follows: glycidyl methacrylate, perfluorododecylethylene and toluene are added to a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 75-85° C., an initiator is added to the reactor, the reaction is carried out by heat preservation for 6-8 hours, and the modified epoxy resin is obtained by post-processing; The preparation method of the reinforcing agent is as follows: adding modified polysiloxane, modified nanoparticles and methanol into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to reflux the system, heat preservation for 2-3 hours, and post-processing to obtain the reinforcing agent; The modified polysiloxane is processed by the following steps: A1. Add isocyanatepropyltriethoxysilane, dopamine hydrochloride and tetrahydrofuran solution into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to reflux the system, keep the temperature for 4-6 hours, and perform post-treatment to obtain modified siloxane. A2, aminopropylmethyldiethoxysilane, octamethyl silicone oil, modified siloxane, and tetrahydrofuran are added to a reaction kettle and stirred, the temperature of the reaction kettle is increased to reflux, potassium hydroxide solution is added to the reaction kettle, and the reaction is kept warm for 10-12 hours, and post-processed to obtain modified polysiloxane; The modified nanoparticles are obtained by processing the following steps: B1. Add nano zinc oxide, 5-hexenyltrimethoxysilane and anhydrous ethanol into a reactor, disperse by ultrasonic for 30-50 minutes and then stir, add sodium hydroxide solution into the reactor, increase the temperature of the reactor to 50-60°C, keep the temperature for 5-7 hours, and perform post-treatment to obtain activated nanoparticles; B2. Add activated nanoparticles, 1-allyl-3-methylimidazolium chloride, maleic anhydride, N,N-dimethylformamide and initiator into a reactor and stir. Raise the temperature of the reactor to 55-65°C and keep the reaction temperature for 6-8 hours. Post-treat to obtain modified nanoparticles.

2. The antistatic and corrosion-resistant nitrile gloves according to claim 1, characterized in that: The dosage ratio of the initiator of glycidyl methacrylate, perfluorododecylethylene and toluene is 3g:1-2g:15mL:0.02g, the initiator is dibenzoyl peroxide, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is kept at 75-85°C, and the solvent is evaporated under reduced pressure to obtain a modified epoxy resin.

3. The antistatic and corrosion-resistant nitrile gloves according to claim 1, characterized in that: The usage ratio of the modified polysiloxane, the modified nanoparticles and the methanol is 3g:2g:30mL. The post-treatment comprises: after the reaction is completed, the reactor is kept warm and refluxed, and the solvent is evaporated under reduced pressure to obtain the reinforcing agent.

4. The antistatic and corrosion-resistant nitrile gloves according to claim 1, characterized in that: In step A1, the tetrahydrofuran solution is composed of sodium hydroxide and tetrahydrofuran in a ratio of 1g:10mL, the isocyanatepropyl triethoxysilane and dopamine hydrochloride in a ratio of 1mol:1mol, and the hydrochloric acid dopamine and tetrahydrofuran solution in a ratio of 1g:10mL. The post-treatment operation includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filtrate is transferred to a rotary evaporator with a water bath temperature of 45-50°C, and the solvent is evaporated under reduced pressure to obtain a modified siloxane; in step A2, the aminopropylmethyldiethoxysilane, octadecyl silane, The dosage ratio of methyl silicone oil, modified siloxane, tetrahydrofuran and potassium hydroxide solution is 1g:3g:1g:20mL:7mL, the mass concentration of the potassium hydroxide solution is 10-15%, and the post-treatment comprises: after the reaction is completed, the reaction kettle is kept warm and refluxed, the solvent is evaporated, the temperature of the reaction kettle is lowered to room temperature, purified water and chloroform are added to the reaction kettle, stirred at room temperature for 10-15min, allowed to stand for separation, the organic phase is washed with purified water 3 times and then transferred to a rotary evaporator with a water bath temperature of 40-50°C, and the solvent is evaporated under reduced pressure to obtain modified polysiloxane.

5. The antistatic and corrosion-resistant nitrile gloves according to claim 1, characterized in that: In step B1, the dosage ratio of the nano zinc oxide, 5-hexenyltrimethoxysilane, anhydrous ethanol and sodium hydroxide solution is 3g:1g:15mL:5mL, the concentration of the sodium hydroxide solution is 0.1-0.2mol / L, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C and dried to constant weight to obtain activated nanoparticles; step In B2, the amount ratio of the activated nanoparticles, 1-allyl-3-methylimidazole chloride, maleic anhydride, N,N-dimethylformamide and initiator is 3g:2g:1g:20mL:0.05g, the initiator is azobisisobutyronitrile, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with anhydrous ethanol for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60°C, and dried to constant weight to obtain modified nanoparticles.

6. The method for preparing an antistatic and corrosion-resistant nitrile glove according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, adding modified epoxy resin, carboxyl nitrile latex, reinforcing agent, tetrahydrofuran and additives into a reactor and stirring, raising the temperature of the reactor to 50-55° C., keeping warm and stirring for 20-30 minutes, passing through an 80-mesh sieve to obtain a dipped latex; S2, cleaning and drying the hand mold, immersing the hand mold in a demoulding liquid to form a film layer on the outside of the hand mold to obtain a pretreated hand mold; S3, immersing the pretreated hand mold in a dipping latex, and after the dipping latex is leached out, immersing it in a coagulation bath to form a uniform film on the outside of the hand mold, and post-treating to obtain a nitrile film; S4, curling the nitrile film to form an elastic rubber ring at the wrist of the glove, closing the mold, and heat-setting to obtain a crude nitrile glove; S5, washing the crude nitrile gloves with chlorine, drying them, and then demoulding them to obtain nitrile gloves.

7. The method for preparing the antistatic and corrosion-resistant nitrile gloves according to claim 6, characterized in that: In step S1, the additives are composed of an antioxidant, a dispersant and a plasticizer in a weight ratio of 1:1:3, the antioxidant is one or more combinations of antioxidant RD, antioxidant BLE and antioxidant D, the dispersant is one or more combinations of zinc stearate, sodium stearate, calcium stearate and magnesium stearate, and the plasticizer is one or more combinations of dioctyl phthalate, dibutyl phthalate, diethyl phthalate and dinonyl phthalate; in step S2, the demoulding liquid is 8-10wt% calcium chloride solution, and the temperature of the demoulding liquid is 55-65°C; in step S3, the coagulation bath is calcium nitrate, starch, gum arabic, phenol and soft water in a weight ratio of 40:1.5:1:0.5:150, the post-treatment comprising: washing the film twice with soft water, and using compressed air purified by a 3M filter element to blow dry the water stains on the surface of the film after each washing to obtain a nitrile film; in step S4, the heat setting temperature is 115-125° C.; in step S5, the chlorine washing and drying operations are as follows: completely immersing the hand mold with the crude nitrile gloves on the outside in a chlorine solution with an active chlorine content of 500-1000 mg / L, ultrasonically treating for 15-25s, washing twice with soft water, and using compressed air purified by a 3M filter element to blow dry its surface after each washing.

Citation Information

Patent Citations

  • Antistatic butyronitrile glove and preparation method thereof

    CN109837766A

  • Pair of novel antistatic butyronitrile gloves and preparation method thereof

    CN111333928A